Quality of Higher Studies Assessment in one of Bagdad University Faculties Based on Some Factor Affect it - Raad Altaey; Sabeha Kasem; Mahmood Al-Wadi (University of Science and Technology, Yemen, 2013)
Abstract               This research consider evaluation of higher studies' quality , depending on concepts and methodology used for measuring quality of service. " Service Performance " ( SERVPERF ) methodology for service quality measurement was used to measure higher studies' quality .A sample included (40) students in Administration & Economic College at Baghdad University               Objectives of research included measurement of  teaching process quality in higher studies , define variables and dimensions of service quality influence quality of higher studies and study the impact of some factors ( "Faculty Members " , " Curriculum" , " Student" , " Management" , " Physical Facilities" ) on the quality of the teaching process in higher studies.                      The study found that the overall quality of higher studies  above the average. Only  half of  quality dimensions ("Access" ,  " Communication " , "Security" ,  "Credibility" ,  "Understanding Student") had  high rate .Dimensions of " Competence " ,  "Reliability" ,  " Responsiveness "and " Courtesy" had above average rate. Dimension of " Tangibles" had under average rate. Variables being considering their impact on higher studies had ,  in the best condition ,  above average rate. Other variables("Availability" for " Faculty Members " , "Scientific Eligibility" ,  and "Legal Eligibility " for" Student") had under average rate. The study  also found significance relationship between quality of higher studies service and the five variables of service quality . Variables had stronger influence on the quality of higher studies service were respectively: " Assurance"  ,  " Tangibles " , " Responsiveness ". Finally the study found significance relationship between higher studies quality and variables of " Faculty Members " , " Curriculum" , " Student" , "Management" ,     " Physical Facilities ".Variables of "Systems" for "Management" and "Equipment and Tools" for "Physical Facilities" had stronger effect  on the quality of higher studies service